Large-scale sequencing paves the way for genomic and genetic analyses in parasitic plants. (August 2021) - Yoshida, Satoko; Kee, Yee Jia
Graphical abstract: Highlights: Genome sequences of parasitic angiosperms reveal unique evolutionary features. Frequency of gene losses and horizontal gene transfers correlates with host dependency. Interspecifically mobile small RNAs and proteins promote fitness for plant parasitism. Comparative transcriptome and reverse genetics reveal functional genes involved in plant parasitism. Genome sequencing technology enabled forward genetics in a model parasitic plant. Abstract : Parasitic plants pose a serious agricultural threat, but are also precious resources for valuable metabolites. The heterotrophic nature of these plants has resulted in the development of several morphological and physiological features that are of evolutionary significance. Recent advances in large-scale sequencing technology have provided insights into the evolutionary and molecular mechanisms of plant parasitism. Genome sequencing has revealed gene losses and horizontal gene transfers in parasitic plants. Mobile signals traveling between the parasite and host may have contributed to the increased fitness of parasitic life styles. Transcriptome analyses implicate shared processes among various parasitic species and the establishment of functional analysis is beginning to reveal molecular mechanisms during host and parasite interactions.